Measurement Football Physical Tests Using an Outdoor Laboratory at an Educational Park - Bongga, Rizki Dwi Oktario; Hartati, Hartati; Aryanti, Silvi (Department of Physical Education, Sport, Health and Recreation, 2024)
This study aims to assess the physical fitness of male students at Indralaya 1 Public Middle School through a descriptive research approach using a quantitative method, employing normality and percentage tests for data analysis. The study included the entire student population of Indralaya 1 Public Middle School, with a sample of 30 male students selected through total sampling. Physical fitness was measured using tests for explosive power, endurance, speed, strength (arm and abdominal muscles), agility, and flexibility. Data analysis involved the Smirnov Kolmogorov normality test and percentage calculations using Excel and SPSS 22. The findings revealed that the overall physical condition of the students in the soccer tests was categorized as pretty good, with an average result of 50.14%. The specific test results were as follows: explosive power 60%, endurance (bleep test) 60%, speed (40m run) 67%, strength (push-ups and sit-ups) 57%, agility 57%, and flexibility 50%. In conclusion, students at Indralaya 1 Public Junior High School a reasonably good physical condition based on soccer-related assessments. The practical implication of this research is that physical fitness significantly contributes to daily activities, particularly in the context of Physical Education and Sports football lessons.